A New Regulatory Road-Map for Alzheimer’s Disease Drug Development - E. Becker, Robert; H. Greig, Nigel (Current Alzheimer Research, 2014)
A surfeit of errors and an absence of sufficiently rigorous neuroscience theory have led to failures of neuroscience drug developments and to less effective patient care. Alzheimer’s disease (AD) requires systematic grounding of drug developments with mechanistic explanations to replace current trial and error approaches to the development of potential drug products. We foresee the need for regulatory revisions that will provide better balanced supports for advancing the AD scientific knowledge required to more effectively develop clinically useful drugs and for provisions to patients of drug candidates soundly predicted, based on documented effects on AD neuropathologies and safety, to slow or arrest the progression of persons at-risk to AD dementia. We propose that investigators and regulators focus AD clinical research on understanding the inductions of reversible and irreversible neuropathologies and their roles in generating clinical dementia. In support of this, we foresee the need for regulatory changes to create a vehicle for these clinical studies; for example, conditional drug approvals based on drug induced neuropathological changes.
Keywords: Alzheimer’s disease